Implementation of efficient fast charger using pulse-charging method and optimized temperature - Sadmani, Saffat Newaz; Hossain, Md. Tanvir; Emon, Md. Taohidul Haque; Rahman, M Mustafizur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.